Mathematical principles of remote sensing making interferences from noisy data - Milman Andrew S (Chelsea Ann Arbor Press, 1999)
Mathematical Principles of Remote Sensing is an informative reference, or working textbook, on the mathematics, and general physical and chemical processes behind remote sensor measurements. The issues and mathematical principles important to remote sens
Keywords: Remote sensing-mathematical models